Assessing the Cybersecurity Risks Associated with the Internet of Things (IoT) Devices - Akintayo, Taiwo Abdulahi; Asolo, Emmanuel; Nnamani, Chinenye Cordelia; Felix, Omojola Ayogoke; Osaro, Chukwuemeka Chukwuma; Atinuke, Aregbesola Taobat (Mikailalsys Journal of Advanced Engineering International, 2024)
The rapid rise of the Internet of Things (IoT) in our daily lives has brought significant cybersecurity concerns to the forefront, emphasizing the need for both active and proactive measures. This research provides a comprehensive review of the literature on the cybersecurity challenges and threats faced by various IoT devices. It outlines proposed solutions and structural frameworks while also exploring different methods for detecting and identifying potential threats. Additionally, it highlights research gaps within the industrial and economic sectors of IoT applications. Our findings reveal that the main issues affecting IoT systems include cybercrime and privacy violations. While Artificial Intelligence holds great promise for enhancing cybersecurity, many attacks, particularly those focused on authentication and confidentiality, are still inadequately addressed by existing solutions. This indicates a pressing need for further research and practical testing of the recommended defenses.